Está en la página 1de 2

EVALUACION 1

Resuelve las siguientes sumas de fracciones algebraicas con


denominador monomio.
Escribir el desarrollo paso a paso.

1.

= 3(x-2) + 2(3x+2) /12 = 3x-6+6x+4/12= 9x-2/12

2.
= 4b(a-2b) +3a (b-a) /60ab = 4ab-8b+3ab-3a/60ab =
7ab-8b-3a/60ab

3.
11a/12

4.

= 4(a-1)+2(2a)+1(3a+4)/12 = 4a-4+4a +3a +4 /12 =

2 +1 / 30ab = 6b(2) +10a(1)/30ab = 12b-10a/30 a3b

5.
=
n+3m+2mn/ mn

n+3+2/mn = n(m) + m(3) + mn(2) / mn =

6.
12ab/15ab =

= 5ab(a+3b) +3(ab -4ab) /15ab = 5ab +15b+3ab8a+15b-12ab/15ab

7.
= 6x(3) +15x(x+2)+5(x+2) / 30x=
18x+15x+30x+5x+10x/30x=
48x+30x/30x

8.
= 3x(1-x) +6(x+2)+2a(1)/ 6x = 3x3x+6x+12x+2a/6x = 18x+2a/6x

9.
=
10x(2a-3)+3a(3x+2)+6(x-a)/30ax = 20ax30x+9ax+6x+6a+6x-6a/30ax = 29ax-24x/30ax

10.
= 15x(x-2) +9(x-2) +5(2-3x) /45x = 15x-30x+9x18+10x-5x4 /45x= 24x-20x-18-5x4/ 45x

11.
= m(a+3b)+b(2a -3m) +bm(3) /abm =
am+3bm+2ab-3bm+3bm/abm
= am+2ab+3bm/abm

12.
a3+ab+b3/ab3

= ab(1) +a(b-a) +b(ab+b)/ab3 = ab+ab= 3ab-a3+b3/ab3

13.
am+2an-mn/amn

a(m-n) +m(n-a) +n(2a-m) /amn = am-an+mn= an/amn

14.
= 5(x-y) +4(2x+y) +2(y-4x) /60 = 5x5y+8x+4x+2y-8x/60 = 9x-3y/60